Use of Recombinant Antigens for Early Postnatal Diagnosis of Congenital Toxoplasmosis - Buffolano, Wilma; Beghetto, Elisa; Del Pezzo, Mariassunta; Spadoni, Andrea; Di Cristina, Manlio; Petersen, Eskild; Gargano, Nicola (JOURNAL OF CLINICAL MICROBIOLOGY, 2005)
The main objective of this work was to improve the early serologic diagnosis of toxoplasmosis in children at risk of congenital infection by using recombinant antigens. Serum samples from 104 infants born to mothers with primary Toxoplasma gondii infection acquired during pregnancy, of which 35 were congenitally infected and 22 had clinical silent toxoplasmosis at birth, were included. Immunoglobulin M (IgM), IgG, and IgG subtype antibodies against epitopes carried by fragments of T. gondii MIC2, MIC3, MIC4, M2AP, AMA1, and SAG1 gene products were measured by performing parallel enzyme immunoassays (Rec-ELISAs). Recombinant antigens preferentially reacted with IgG antibodies from infected infants compared to uninfected subjects (P < 0.0001), indicating that sera from infected children recognized a more diverse repertoire of antigens than sera transferred over the placenta from the mothers. Using two serial samples collected within 3 months of life, it was possible to demonstrate a neosynthesis of specific anti-MIC2 and anti-SAG1 immunoglobulin G, mainly of the IgG2 subtype, in 13 out of 20 infants with congenital toxoplasmosis. IgM antibodies in 97% of infected infants reacted with at least one of the recombinant antigens, confirming the diagnosis of congenital infection as soon as 2 months after birth (P < 0.0001). The use of recombinant antigens is effective in distinguishing T. gondii-infected from uninfected infants and shows that assays based on recombinant antigens improve the diagnosis of newborns with congenital toxoplasmosis.